Hoot - Hiaasen, Carl (New York Alfred A. Knopf, 2002)
Roy, who is new to his small Florida community, becomes involved in another boy's attempt to save a colony of burrowing owls from a proposed construction site.
Keywords: Burrowing owl -- Fiction; Owls -- Fiction; Environmental protection -- Fiction; Florida -- Fiction